What's wrong with fat the war on obesity and its collateral damage - Saguy, Abigail Cope, 1970- (New York : Oxford University Press, 2013)
This study presents each of the various ways in which fat is understood in America today, examining the implications of understanding fatness as a health risk, disease, and epidemic, and revealing why we have come to understand the issue in these terms, despite considerable scientific uncertainty and debate. The book shows how debates over the relationship between body size and health risk take place within a larger, though often invisible, contest over whether we should understand fatness as obesity at all. Moreover, it reveals that public discussions of the 'obesity crisis' do more harm than good, leading to bullying, weight-based discrimination, and misdiagnoses.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references and index.
Keywords: Obesity -- Social aspects